Dynamic analytical modeling of horizontal outline turn of T-girder simply supported bridge - Naser, Ali Fadhil (Penerbit Universiti Kebangsaan Malaysia, 2021)
Layout line of bridge structure is a direction line which is used to define the horizontal and vertical alignment of the bridge structure. The objective of this study is to evaluate and optimize the different designs of bridge horizontal outline turn and compare the results with horizontal layout straight of bridge using dynamic analysis according to finite element analysis method. Dynamic analysis results showed that most models have converging values of dynamic natural frequency except Model No. F. and it explains that the higher rate of natural frequency is 5.10Hz within model No. F. The maximum value of loaded frequency is equal to 6.35 Hz for model No. I (Straight - curve right - straight - curve left - straight). Model No. A appears minimum value of loaded frequency which equal to 3.56Hz. The higher value of loaded frequency indicates that the bridge model has high vibration state which effects on the stiffness and flexibility of bridge structure. Model No. I appears higher value of downward acceleration which is 3.55m/s2. The maximum value of upward and downward deflection is 1.84mm and 4.07mm respectively in model No. G, indicating that this model will easy to deflect under traffic loads. It can be concluded that The bridges models No. F, H, I have values of loaded frequency higher than the values of natural frequency. Therefore, these models have lower stiffness and flexibility and bearing capacity than other. Therefore, this study recommended that the optimum design which has high stiffness and more elasticity.